2013
DOI: 10.1016/j.cell.2013.05.052
|View full text |Cite
|
Sign up to set email alerts
|

Lipidomic Profiling of Influenza Infection Identifies Mediators that Induce and Resolve Inflammation

Abstract: Summary Bioactive lipid mediators play a crucial role in the induction and resolution of inflammation. To elucidate their involvement during influenza infection, LC/MS lipidomic profiling of 141 lipid species was performed on a mouse influenza model using two viruses of significantly different pathogenicity. Infection by the low pathogenicity strain, X31/H3N2, induced a pro-inflammatory response followed by a distinct anti-inflammatory response; infection by the high pathogenicity strain, PR8/H1N1, resulted in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
220
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 225 publications
(233 citation statements)
references
References 62 publications
13
220
0
Order By: Relevance
“…3C) (18). As expected, the cytokine level of flu-infected animals was higher than that of its naive controls, confirming previous results (21,22). There was a significant (p , 0.001) difference in the levels of IL-1a, IL-6, and MIP-1a produced in the lung of B27/ERAP +/+ and B27/ERAP 2/2 Tg mice (Fig.…”
Section: Characterization Of Novel B7/erapsupporting
confidence: 88%
“…3C) (18). As expected, the cytokine level of flu-infected animals was higher than that of its naive controls, confirming previous results (21,22). There was a significant (p , 0.001) difference in the levels of IL-1a, IL-6, and MIP-1a produced in the lung of B27/ERAP +/+ and B27/ERAP 2/2 Tg mice (Fig.…”
Section: Characterization Of Novel B7/erapsupporting
confidence: 88%
“…Consistent with impaired peroxisomal ␤ -oxidation, we observed an enrichment in C26:0 but a decrease in C24:1 fatty acids in SPL species ( Fig. 1G ) (25)(26)(27); this provided further support for an important role of fatty acyl metabolism during infl uenza infection ( 15,16 ).…”
Section: D609 and Gw7647 Treatment Of Infl Uenza Virus-infected Cellssupporting
confidence: 73%
“…Host cell lipid metabolism and plasma membrane microdomains are implicated in the biogenesis of virus envelopes. Several studies have dissected the lipid inventory of purifi ed infl uenza virions ( 9, 10 ), whereas others have demonstrated the requirements for de novo fatty acid and sphingolipid biosynthesis and unique cholesterol compositions for virus production at budding sites (11)(12)(13)(14).In addition to the importance of host cell lipid metabolism for the biogenesis of infl uenza virus envelopes, recent fi ndings suggest a major role for soluble lipid mediators in antiviral responses against infl uenza virus infection in vivo ( 15,16 ). These soluble lipid mediators originate from membrane glycerophospholipids (GPLs) via phospholipase activity, and (to some extent), are metabolized in peroxisomes.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, we studied the effects of fish oil consumption on Lyme disease progression (174). In this research, novel eicosanoid mediators were found, including anti-inflammatory mediators that differentiate the pathogenicity of influenza strains in mouse and in human lavages (175). Lipidomic analysis of cells supplemented with small amounts of the fish oil-derived -3 fatty acids, eicosapentaenoic acid (EPA) or docosahexaenoic acid (DHA), clarified their effects on the inflammatory eicosadome in inhibiting COX-1 more than COX-2 and shunting arachidonate to LOX physiologically (176).…”
Section: Lipidomics Of Fatty Acids and Eicosanoidsmentioning
confidence: 99%